Family mediation, another way of approaching and resolving conflicts (Journal of Parents and Teachers, 2014)
Conflicts should be resolved through dialogue and respect, even if people disagree. Mediation is a way of resolving conflicts through dialogue and listening to others; it is important to remember that everyone has a right to an opinion. Sometimes it is necessary to go to a mediator, someone who must be trained; the main work of the mediator is to make his clients feel heard, all feelings are legitimate. The mediation is to recover the lost calm and to calm the anguish.
Keywords: family crisis; conflict; family; mediator